Efficacy of photodynamic therapy in the treatment of oral premalignant lesions: A systematic review - Arunima Goswami; Bharadwaj Bordoloi; Pinky Goswami; Aanchal Tandon (Wolters Kluwer Medknow Publications, 2023)
Photodynamic therapy (PDT) is considered a contemporary effective treatment option for oral premalignant lesions. This systematic review aims to evaluate the usefulness of PDT for the treatment of oral premalignant lesions. The focused question was "Is PDT effective in the treatment of oral premalignant lesions?" A literature search was made in PubMed/Medline and Google Scholar databases using different combinations of the following keywords: photodynamic therapy, oral premalignant lesions, oral leukoplakia (OL), erythroplakia, oral erythroleukoplakia (OEL), oral verrucous hyperplasia (OVH), and oral lichen planus (OLP). Review articles, preclinical studies, case reports, commentaries, letters to the editor, unpublished articles, studies on photodynamic therapy used in areas other than oral cavity, and articles published in languages other than English were excluded. The relevant information were summarized. Initial results were 23. Twenty-two studies were included. Oral premalignant lesions, which were investigated, were OL, erythroplakia, OEL, OVH, and OLP. The studies used either laser light or light-emitting diode. Photosensitizers used were aminolevulinic acid, chlorine-e6, meta-tetrahydroxyphenylchlorin, methylene blue, toluidine blue, methyl 5-aminolevulinate cream, and phenothiazine chloride. Study outcomes and recurrence rates were evaluated. PDT is an effective treatment option. Topical PDT is an easy-to-perform technique, well-tolerated treatment with encouraging achievements in the treatment of premalignant lesions.